1993
DOI: 10.2166/wst.1993.0113
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Processes in Landfills

Abstract: Large landfills in the Soviet Union cover more than 140 thousand hectares. The gas emission intensities are extremely disproportional over the surface of these landfills. According to our data the rates of streams of the biogas components vary from 0 till 20, 46, 1.2 and 0.75 (×10−4m3 × hour −1/m2) for CH4, CO2, H2, CO, respectively. The stable carbon isotope composition of methane and carbon dioxide in the biogas of deep landfills layers is typical for methanogenesis from organic wastes, but it depends on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Further, these models do not consider methane movement and its oxidation in the final cover, although there are models developed independently for this purpose [33,34,42]. Methane oxidation in covers can range between 10% and 70% of methane generated in a landfill [11,23,30,51].…”
Section: Introductionmentioning
confidence: 99%
“…Further, these models do not consider methane movement and its oxidation in the final cover, although there are models developed independently for this purpose [33,34,42]. Methane oxidation in covers can range between 10% and 70% of methane generated in a landfill [11,23,30,51].…”
Section: Introductionmentioning
confidence: 99%
“…In the solid waste management, landfill is one of the most prevalent methods used by many countries in the world [1]. With approximate calculations, it is found that 450-500 million tonnes of domestic solid waste is produced annually in the world [2]. Three hundred and twenty to three hundred and fifty million tonnes of this, that is equivalent to 70%, is removed by landfill [3].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial CH 4 oxidation depends on several abiotic variables such as the soil's water content, temperature, CH 4 concentration, oxygen (O 2 ) availability, and nutrients concentrations Bogner et al, 1997b;Börjesson et al, 1998a;Börjesson et al, 2004;Christophersen et al, 2000;Czepiel et al, 1996a;De Visscher et al, 2001;Figueroa, 1993;Hilger et al, 2000;Kightley et al, 1995;Nozhevnikova et al, 1993;Watzinger et al, 2005;Whalen et al, 1990). Less attention has been paid to soil texture and physical characteristics such as compaction and air-filled porosity (Figueroa, 1993;Kightley et al, 1995), which all affect the movement of gases in soil (Hillel, 1998) and thus CH 4 oxidation in the field.…”
Section: Introductionmentioning
confidence: 99%